Prevalence and trends of overweight and obesity amongst Saudi school children, a study done by using three noninvasive methods - Shaikh, Masood Ahmed; Al Sharaf, Fawazy; Shehzad, Khalid; Shoukat, Faiza; Naeem, Zahid; Al Harbi, Sultan; Almutairi, Ahmad Saeed; Al Ilaj, Muath Owaidh; Al Motairi, Sultan (International Journal of Health Sciences, 2016)
Obesity has become a global epidemic. It’s level in the Middle Eastern and Asian countries have reached to an alarming level. Rapid transition of life style and urbanization has not only affected adults but also the younger population. Objective: This study records the trends of prevalence of obesity and over weight in the school children of both genders of Al Qassim region by employing three different non-invasive methods and recorded their differences. Subjects and methods: This cross-sectional study was conducted on Saudi students of secondary and intermediate levels between 12-14 years of age. The total number of the students who participated in the study was 242, 129 males and 113 females. A self-administered pre-coded questionnaire was used. Body mass index, skin fold thickness and bioelectrical impedance analyzer (BIA) readings were recorded. Data was analyzed on SPSS version 11. Descriptive statistical analysis was performed. Chi square test with a P value <0.05, was used to compare the prevalence rates. Results: Prevalence of obesity and over-weight recorded were higher in the boys but the rates recorded by three methods have shown a wide variation. Several factors, such as change in dietary habits, socioeconomic status and the family history of obesity have shown association but physical inactivity and father’s obesity were found significant contributory factors. There is an urgent need for intervention to prevent and control obesity and its consequences amongst children in Saudi Arabia.